Where They Last Saw Her : a novel - Rendon, Marcie R. (New York : Bantam, 2024)
"From the award-winning author of the Cash Blackbear series, a harrowing novel of a Native American woman who learns of the disappearance of one of her own and decides enough is enough... All they heard was her scream. Quill has lived on the Red Pine reservation in Minnesota her whole life. She knows what happens to people who look like her. Just a girl when Jimmy Sky jumped off the railway bridge and she ran for help, Quill realizes now that she hasn't ever stopped running. As she trains for the Boston Marathon early one morning out in the woods, she hears a scream. When she investigates, she finds tire tracks and a lone, beaded earring. Things are different now for Quill than when she was a lonely girl. Her friends Punk and Gaylyn are two women who don't know what it means to quit; she has her loving husband, Crow, and two beautiful children who challenge her to be better every day. So when she realizes another woman has been stolen, she is determined to do something-and her first stop is the group of men working the pipeline construction just north of their homes. As Quill closes in on the truth behind the missing woman in the woods, someone else disappears. In her quest to find justice for the women of the reservation, she is confronted with the hard truths of their home and the people who purport to serve them. When will she stop losing neighbors, friends, family? As Quill puts herself, her family, and everything she's built on the line to make a difference, the novel asks searing questions about bystander culture, the reverberations of even one act of crime, and the long-lasting trauma of being invisible"--.
new book 2024 fall.
Keywords: Indian women -- Fiction -- Crimes against -- United States; Abduction -- Fiction; Detective and mystery stories; Crimes against; Women runners; Novels